Planned and emergency hospital admissions of 1.2 million adult non-EU migrants and refugees in England - Burns, Rachel; Wyke, Sacha; Boukari, Yamina; Eyre, Max T; Nyguyen, Vincent; Pathak, Neha; Lewis, Kate M; Stevenson, Kerrie; Hiam, Lucinda; Zenner, Dominic; Campos-Matos, Ines; Harron, Katie; et al. (International Journal of Population Data Science, 2025)
Objective Utilisation of health services is an important indicator of migrants’ access to healthcare, but there is little and mixed evidence on access to and use of secondary care by migrants living in England. Understanding migrant healthcare utilisation by visa type and region of origin will help identify important trends and inequities. Method A linked retrospective longitudinal cohort was used to estimate patterns of hospital admission rates for over 1.2 million adult non-EU migrants and resettled refugees compared to the general population in England between April 1, 2007, through March 23, 2020. Negative binomial regression models were fitted to model associations between visa type and region of origin and the risk of emergency and planned hospital admissions. Results Emergency and planned hospital admissions were lower for almost all migrant sub-groups compared to the general population in England, particularly for those on student, work, and working holiday visas. For less than 3% of the migrant cohort, higher planned admissions for male refugees (IRR 2.28; 95% CI 1.38-3.78) and higher emergency admissions for female refugees (IRR 1.71, 95% CI 1.28-2.28) and family visa holders (IRR 1.28, 95% CI 1.05-1.57) were identified. Conclusion Most migrant groups have a lower usage of NHS emergency and planned secondary care services than the general population in England, though differences by visa type and region of origin exist.